PENGARUH STRATEGI MARKETING MIX TERHADAP KEPUASAN PELANGGAN ( Studi Kasus Pada CafÃ© FHO ( Funtastic Hangout ) di Samarinda ) - Fami, - - (EKONOMIA, 2019)
The purpose of the study was to determine and analyze the influence of marketing mix strategies: product, price, place, promotion, people, physical evidence, and the process of customer satisfaction at Cafe Funtastic Hangout in SamarindaThe problems in this are as follows: Is the marketing mix: product, price, place, promotion, people, physical evidence, and process affect customer satisfaction Cafe Funtastic Hangout in Samarinda?Analysis Results: 1) The results of the t test indicate that the Product variable (X1) has no significant effect on Customer Satisfaction directly. Then it can be seen that the relationship of the Product variable (X1) to Customer Satisfaction (Y) is 0.173. 2) The results of the t test show that the Price (X2) variable does not affect Customer Satisfaction directly. Then it can be seen that the relationship of Price (X2) to Customer Satisfaction (Y) is -0.357. 3) The results of the t test show that the Place variable (X3) has a significant effect on Customer Satisfaction directly. Then it can be seen that the relationship of Place variable (X3) to Customer Satisfaction (Y) is 0.519. 4) The result of the t test shows that the Promotion (X4) variable has no significant effect on Customer Satisfaction and it can be seen that the relationship of Promotion (X4) to Customer Satisfaction (Y) is equal to -0.252. 5) The results of the t test show that the People variable (X5) has no significant effect on customer satisfaction. Then it can be seen that the relationship of the People variable (X5) to Customer Satisfaction (Y) is -0.086. 6) The results of the t test indicate that the Physical Evidence (X6) variable has no significant effect on customer satisfaction. Then it can be seen that the relationship of Physical variable (X6) to Customer Satisfaction (Y) is 0.160. 7) The results of the t test show that the Process (X7) variable has no significant effect on customer satisfaction. Then it can be seen that the relationship between Process (X7) and Customer Satisfaction (Y) is -0.195